Report of conference between the executive committee of the Printing and kindred trades Federation and representatives of the International Federation of Bookbinders and kindred trades, the International Lithographers' Federation and the International Typographers' Secretariat (Koordinationskomitee der drei Internationalen Föderationen im graphischen Gewerbe, 1946)
See for german ed.: INT 2661/98.